2013
DOI: 10.5014/ajot.2013.008243
|View full text |Cite
|
Sign up to set email alerts
|

Functional Handwriting Performance in School-Age Children With Fetal Alcohol Spectrum Disorders

Abstract: Handwriting is a critical skill for school success. Children with fetal alcohol spectrum disorders (FASD) often present with fine motor and visual-motor impairments that can affect handwriting performance, yet handwriting skills have not been systematically investigated in this clinical group. This study aimed to comprehensively describe handwriting skills in 20 school-age children with FASD. Children were tested with the Process Assessment of the Learner, 2nd Edition (PAL-II), and the Visuomotor Precision sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The findings are consistent with those of Duval‐White et al . () who found that most children with FASD in their study ( n = 20) scored in the ‘well‐below average’ range for letter legibility.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The findings are consistent with those of Duval‐White et al . () who found that most children with FASD in their study ( n = 20) scored in the ‘well‐below average’ range for letter legibility.…”
Section: Discussionmentioning
confidence: 84%
“…However, despite anecdotal reports of graphomotor impairment in children with FASD (Clarren, ), few studies have reported the quality of handwriting or drawing skills in children with FASD. Those studies have either included only a small, exploratory sample ( n = 20) (Duval‐White, Jirikowic, Rios, Deitz & Olson, ), or have not assessed human figure drawing skills within a motor performance framework (Aronson, Kyllerman, Sabel, Sandin & Olegard, ; Urban et al ., ). Functional assessments of graphomotor skills in children with PAE may assist identification of fine motor impairment during the FASD diagnostic process, improve knowledge of the functional implications of PAE and guide therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of fine motor deficits on alcoholaffected children's functional activities such as writing is unknown. Therefore, Duval-White et al [114] examined functional handwriting performance in school age children with FASD using the Process Assessment of the Learner-2 nd Edition and Visual Motor Precision subtest of the developmental neuropsychological assessment (NEPSY). Results showed that children with FASD performed below average range on handwriting legibility and speed.…”
Section: Motormentioning
confidence: 99%
“…Children and adults with prenatal alcohol exposure (PAE) often have impaired sensorimotor function including gross and fine motor problems, poor motor coordination, and sensory processing deficits (Barr, Streissguth, Darby, & Sampson, 1990;Carr, Agnihotri, & Keightley, 2010;Doney et al, 2014;Duval-White, Jirikowic, Rios, Deitz, & Olson, 2013;Franklin, Deitz, Jirikowic, & Astley, 2008;Jirikowic, Olson, & Kartin, 2008;Jirikowic et al, 2013;Lucas et al, 2014;Mattson, Riley, Gramling, Delis, & Jones, 1998;Riley and McGee, 2005). Previous neuroimaging studies have found abnormal brain structure in the sensorimotor cortex (Archibald et al, 2001;Sowell et al, 2002Sowell et al, , 2008Yang et al, 2012) and its associated white matter connections (Lebel et al, 2008;Wozniak et al, 2009), and altered brain development trajectories of cortical volumes and thickness within the sensorimotor cortex (Lebel et al, 2012;Treit et al, 2014).…”
Section: Introductionmentioning
confidence: 99%